IL-23-responsive innate lymphoid cells are increased in inflammatory bowel disease. - Geremia, A; Arancibia-Cárcamo, C; Fleming, M; Rust, N; Singh, B; Mortensen, N; Travis, S; Powrie, F (2011)
Results of experimental and genetic studies have highlighted the role of the IL-23/IL-17 axis in the pathogenesis of inflammatory bowel disease (IBD). IL-23-driven inflammation has been primarily linked to Th17 cells; however, we have recently identified a novel population of innate lymphoid cells (ILCs) in mice that produces IL-17, IL-22, and IFN-γ in response to IL-23 and mediates innate colitis. The relevance of ILC populations in human health and disease is currently poorly understood. In this study, we have analyzed the role of IL-23-responsive ILCs in the human intestine in control and IBD patients. Our results show increased expression of the Th17-associated cytokine genes IL17A and IL17F among intestinal CD3⁻ cells in IBD. IL17A and IL17F expression is restricted to CD56⁻ ILCs, whereas IL-23 induces IL22 and IL26 in the CD56⁺ ILC compartment. Furthermore, we observed a significant and selective increase in CD127⁺CD56⁻ ILCs in the inflamed intestine in Crohn's disease (CD) patients but not in ulcerative colitis patients. These results indicate that IL-23-responsive ILCs are present in the human intestine and that intestinal inflammation in CD is associated with the selective accumulation of a phenotypically distinct ILC population characterized by inflammatory cytokine expression. ILCs may contribute to intestinal inflammation through cytokine production, lymphocyte recruitment, and organization of the inflammatory tissue and may represent a novel tissue-specific target for subtypes of IBD.